The effect of counseling based on health promotion awareness on self-care needs and reproductive and sexual health literacy of newly married women: a randomized controlled clinical trial study - Fereshteh Kohansal; Roghaiyeh Nourizadeh; Niloufar Sattarzadeh Jahdi; Mahdie Arab Bafrani; Esmat Mehrabi (BMC, 2024)
Abstract Background Despite the importance of health literacy and the self-care skills in improving individual and social health and health costs reduction, scientific evidence indicates women's poor awareness of self-care needs and low health literacy concerning reproductive and sexual health in most societies. The present study was conducted to specify the effect of health awareness promotion on self-care needs and reproductive and sexual health literacy of newly married women. Methods This randomized controlled clinical trial was conducted on 64 newly married women aged 15-45 in Tehran, Iran from August 2021 to the end of December 2021. The participants were randomly assigned into the intervention (n = 32) and control (n = 32) groups. The intervention group received four individual health awareness-promotion education sessions. The reproductive and sexual self-care needs, and sexual health literacy questionnaires, were completed before and 4-week after the intervention through interview. The data were analyzed using SPSS26 software. The independent t-tests and ANCOVA were used to comparison the mean scores and a significance level of P < 0.05 was considered. Results The results of this study indicated that after counseling, the average overall score of perceived reproductive and sexual self-care needs significantly decreased in the intervention group [Mean (standard deviation(SD)): 125.70 (24.70)] compared to the control group [Mean (SD): 87.1 (23.42)][P = 0.001]. Also, the mean score of sexual and reproductive health literacy significantly increased in the intervention group [Mean (SD): 125.50 (14.09)] compared to the control group [Mean (SD): 97.15 (14.90)] after intervention [P = 0.01]. Conclusions The results indicated the positive effect of health promotion awareness educations on reproductive and sexual self-care needs and health literacy among newly married women. Therefore, health promotion interventions should be incorporated in health services provision programs for newly married women in comprehensive health centers to improve the health of women and families. Trial registration Iranian Registry of Clinical Trials (IRCT): IRCT20171007036615N7 Date of registration: 2021-09-21. URL: https://fa.irct.ir/trial/58597 .